(untitled) (Research, Society and Development, 2021)
This study developed a virtual learning environment to support face-to-face teaching of the subject of Mobile Cellular Telephony of a federal institution of professional and technological education that operates in Northern Brazil. The methodology used consisted of quantitative-qualitative research, of a technological nature, developed in seven stages: 1) installation of the XAMPP and Moodle software, 2) configuration of the teaching environment, 3) allocation of the Moodle platform, 4) use of virtual resources interactive, 5) production of learning objects, 6) measurement of environmental performance indicators and 7) analysis and generation of results. The results showed that a) this was the first virtual learning experience for almost all participating students and teachers interviewed, b) teachers and students were motivated to use virtual environments in their teaching and learning activities, since c) the environment proved to be highly efficient and effective in generating effective learning and d) almost all students carried out the evaluation questions without much difficulty, as usually happens with traditional classes. The conclusion was that a discipline planned from the Moodle platform’s perspective has several advantages, such as optimizing study time and the dynamics of classes.